Development of Bittergourd Fermented Beverage Using Response Surface Methodology - C.S. Devaki; K.S. Premavalli (Journal of Pharmacy and Nutrition Sciences, 2012)
Bittergourd (Momordica charantia) is used as a vegetable by the Asian community and is commonly used as an antidiabetic and antihyperglycemic agent. The aim of the present study was to develop nutritionally strengthful, highly acceptable, shelf stable bittergourd beverage by fermented process using statistical software on Response Surface Methodology (RSM). The optimization of the fermentation process with reference to curd concentration and the period has been attempted by using RSM with more emphasis on nutritional and functional considerations. The statistical design gave 13 formulations, where the fermentation process period varied from 6 to 34 hours and curd concentration was from 6.6 to 16.4%. The standard methodology was followed for the analysis of all the parameters studied. The product varied formulations had quinine range of 119 to 327.5 mg%, antioxidants 40.2 – 64.5%, total phenols 30.5 to 42.5 mg%, water soluble vitamins; B1 – 0.07 to 0.81 mg%, B2 – 0.02 to 0.28 mg%, B3 – 0.4 to 1.08 mg%, B6 – 0.04 to 0.32 mg% and vitamin-C – 17.2 to 34.6 mg%. Fermentation time for 30 hours and curd concentration of 15% was the optimized composition with the best fit of desirability 0.80. The product with the good taste and flavour was acceptable with 6.7 score on 9-pont hedonic scale. The fermented bittergourd beverage was preferred to fresh bittergourd juice.